The natural woman: the influence of Charles Baudelaire in Boris Vian’s "L’automne à Pekin" - de Cabo, Mariana; Montecchio, Estefania (Tropelías: Review of Literary Theory and Comparative Literature, 2019)
In an epigraph from L’automne à Pekin (1947), Vian quotes a passage from Baudelaire’s Fusées: «Aimer une femme intelligente est un plaisir de pédéraste». In Baudelaire’s world view, the woman, a purely natural being, guides the man to his lowest instincts and, therefore, to evil. For that reason, the loving relationship with female represents a sadistic and primitive act between a victim and a killer. Our aim is to analyze, based on the baudelairean conception of women, the motive why Vian quotes the XIXth century writer and how much this intertext allows Vian to shape in his novel a presumed stereotyped vision of the feminine gender.